Behavioural Science Application in Vancouver Based Firms - Xishan, Yang; Moore, Larry; Markgraf, Herb (Relations industrielles / Industrial Relations, 1983)
This study aims first at identifying the state of the art of behavioural science applications and its achievements in Western Canada and at reflecting the different views of various parties towards behavioural science so as to help determine the applicability and practical value of behavioural science in the field of management.